Between Legacy and Innovation: Archaeological Data Re-use and Integration, a Case Study from Northern Sudan - Ward, Chloë (Journal of Global Archaeology, 2024)
This article considers the use and potential of historical survey data through the case study of a region in northern Sudan being investigated by the DiverseNile project. The focus is on the usability and integration of archaeological legacy data in current archaeological research and methodologies. This is not always straightforward but such data remain an invaluable resource for current and future archaeological research. The article concludes with the different ways that historical survey data is being used, assessed and changed in order to be fully integrated it into a current research project and the implications that this can have.